Genesize Polymorphism and Pathogenicity in Embryonated Eggs of Mycoplasma Gallisepticum Isolated From Commercial Chickens - Tan, Ching Giap (2008)
Chronic respiratory disease (CRD) is caused by Mycoplasma gallisepticum (MG). Infected birds show respiratory and reproductive problems which lead to severe economic losses in poultry industry. There are only few published data on avian mycoplasmosis in Malaysia, thus, this study was carried out to determine the strain variability and pathogenicity of MG isolates, towards understanding the control of the infection. A total of 4605 samples were collected from chickens and their progeny from various commercial farms using sterile cotton swabs for culturing onto mycoplasma agar. Twenty three (23) MG isolates were obtained from suspected MG infected commercial chickens. Although MG could be isolated from various sites of the host, in this study, choanal and tracheal sites proved to be the best sites in live birds. On the other hand, trachea and airsac samples were the best sites for the detection of MG for chick embryos or chicks. Size variations among polymerase chain reaction products divergence of the MG-specific gene were the basis for strain differentiation. The local isolates exhibited gene size polymorphism in pvpA gene, 16S-23S rRNA intergenic spacer region gene, ermA gene and pMGA or vlhA gene with the presence of insertion or deletion observed in PCR products. However, the gapA gene, LP gene, F-strain-specific DNA fragment gene, CrmB gene, CrmC gene, p47 gene, HMW3-like protein gene and pneumoniae-like protein A gene sequences were constant in size. The embryonated eggs were each inoculated with "pleuropneumonia like organism" (PPLO) broth containing MG strains, via yolk sac. Mycoplasma gal/isepticum embryos, broth inoculated and uninoculated control embryonated eggs were examined at necropsy days 7, 10, 13 and 15 post-inoculation. The pathogenicity of the isolates in chicken embryonated eggs showed variations among each other. The MG isolates and strains that showed a wide variation in genes were examined for virulence in ovo. In this study, the presence of caseous airsac lesion correlated with virulence ofMG and presence of high maternal antibody titer. MG were isolated only in embryos that did not develop any caseous airsac lesions. MG inoculated embryos were polymerase chain reaction (PCR) positive regardless of the absence or presence of caseous airsac lesion, suggesting that caseous airsac lesion maybe the result of formation of antigen-antibody complex. Caseous airsacs were found to be one of the prominent lesions associated with MG infection. For certain highly pathogenic strains, there was clear relationship between the caseous airsac lesion and the presence of maternal antibody titer and embryo mortality. Less pathogenic strains that grow well usually caused embryo mortality during later stages of incubation and there was no strict correlation between caseous airsac lesion and the presence or absence of maternal antibody and embryo mortality. Based on the presence of the gene size polymorphism in pvpA gene and pMGA or vlhA gene; MGS6 (reference strain), 144 and 1-18 strains of MG showed a similar pattern of pathogenicity in that they are highly pathogenic, whereas, H21 8T, H21 lIT, H24 5C and H26 9C have similar pattern of molecular characterization and pathogenicity with ts-l1 (vaccine strain), characterized by their less pathogenicity in embryos. MGS6, 144 and 1-18 strains caused early embryonic death compared to ts-11, H21 8T, H2 1 lIT, H24 5C and H26 9C strains that caused embryo mortality during later stages of incubation. At this point, the postulation is that, when maternal antibody of MG is high and MG challenge is present, caseous airsac may occur. This would be due to maternal antibody in the eggs which may bind to MG that served as antigen to form antigen-antibody complexes. The immune complexes may help to release cytokines and attract more macrophages and other inflammatory cells, which help to increase the severity of the air sac lesion. When the MG strain with the gene size polymorphism in pvpA gene and pMGA or vlhA gene that has similar pattern with MGS6, it correlates with the formation of caseous air sac, as well as the increase in severity of the caseous airsac. This study showed that the combination of the gene size polymorphism in pvpA gene and pMGA or vlhA gene can be used as pathogenic markers for MG in determination of its pathogenicity towards chick embryos. Based on characterization and pathogenicity, MG field strains H2 1 8T, H21 HT, H24 5C and H26 9C showed similar pattern of molecular and pathogenicity characteristic with ts-l1 and therefore are potential candidates for live MG vaccine.